The Qur’anic Concept of Ownership Over the Land of Jerusalem: A Thematic Tafsir Study of Human Civilization: (Konsep Kepemilikan Qur’ani atas Tanah Yerusalem: Kajian Tafsir Tematik Sejarah Peradaban) - Jabar, Abdul; Naim, Mohammad A’mmar Bin Mohd; Falahan, Azhar Ahmad; Huda, Nurul; Rusdi, Rusdi (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This study addresses the scholarly problem of the use of religious texts as a basis for territorial legitimization over Jerusalem in contemporary historical-political discourse. While numerous exegetical studies discuss the city’s sanctity and prophetic history, there remains no systematic conceptual formulation of a Qur’anic model of ownership and sovereignty over the territory. This absence constitutes the research gap addressed in this article. Employing a qualitative method through thematic exegesis (tafsir mawduʿi) grounded in conceptual analysis, the study examines Qur’anic verses related to al-arḍ, al-arḍ al-muqaddasah, and al-masjid al-aqṣa. These verses are analyzed in light of classical and contemporary interpretations and reconstructed to identify patterns of legitimacy, conditions of inheritance (warathah), the concept of istikhlaf, and mechanisms of mandate revocation in prophetic history. The findings reveal that the Qur’an articulates a theocentric and conditional concept of ownership: the earth belongs to God, while human authority constitutes a moral trusteeship subject to ethical evaluation and possible withdrawal. The study’s novelty lies in demonstrating that the Qur’an not only rejects ethnically grounded territorial claims but also corrects genealogical claims over Prophet Abraham as a foundation of territorial legitimacy by affirming that those closest to Abraham are Prophet Muhammad and those who uphold his monotheistic faith. Theoretically, this article proposes the model of Divine Conditional Sovereignty, a framework of delegated and morally contingent divine authority.